Project-Based Learning and Vocational Self-Concept as Predictors of Employability Skills among Grade XII Vocational High School Students in Gorontalo - Sunardi Sunardi; Lanto Mohamad Kamil Amali; Buyung R. Machmoed; Jumiati Ilham; Hasmah Hasmah (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examined project-based learning and vocational self-concept as predictors of employability skills among Grade XII vocational high school students in Gorontalo, Indonesia. Methods: A quantitative correlational design was used with 215 students selected through proportional random sampling. Data were collected using questionnaires measuring project-based learning, vocational self-concept, and employability skills, and analysed using descriptive statistics, assumption tests, simple regression, and multiple regression. Findings: The descriptive results indicated that students’ responses were predominantly distributed in the high category for project-based learning experience, vocational self-concept, and employability skills. Project-based learning significantly predicted employability skills, R² = 0.471, F (1, 213) = 189.746, p < .001. Vocational self-concept also significantly predicted employability skills, R² = 0.519, F (1, 213) = 229.476, p < .001. Together, both predictors explained 62.3% of the variance in employability skills, R² = 0.623, adjusted R² = 0.620, F (2, 212) = 175.467, p < .001. Vocational self-concept showed a slightly stronger standardized contribution than project-based learning in the simultaneous model. Research implications: Vocational high schools should integrate authentic project-based learning with career-oriented reflection, mentoring, and vocational identity development. Originality: This study integrates a pedagogical predictor and an identity-based predictor in a single employability model within a regional Indonesian vocational education context.